DISPUTE RESOLUTION THROUGH ARBITRATION IN SALE AND PURCHASE AGREEMENT - Daudsyah, Teuku; Lubis, Muhammad Ansori (Jurnal Ilmiah METADATA, 2025)
Dispute resolution outside the court can be grouped into two forms: dispute resolution carried out by the parties themselves and dispute resolution involving a third party. Regarding the involvement of this third party, it is also distinguished into two forms: a third party without decision-making authority (for example, a mediator) and a third party with decision-making authority. The legal force of an arbitration decision is the legal force for the disputing parties. is binding and must be implemented by the parties voluntarily. If the parties are unwilling to comply with the arbitration decision voluntarily, then the arbitration decision will be enforced. If any party objects to the arbitration body's decision, they can file an appeal. Objections must be filed within 14 (fourteen) working days from the time the business actor or consumer receives notification of the Consumer Dispute Resolution Body's decision